Clozapine is responsible for the in vivo imaging and pharmacological effects of clozapine-N-oxide in murine DREADD models - Wang, Jian; Qin, Jiale; Kumata, Katsushi; Zhang, Ming-Rong; Qian, Jun; Zhou, Wen; Ji, Bin (Frontiers in Pharmacology, 2025)
Although clozapine-N-oxide (CNO), a major metabolite of clozapine (CLZ), is a widely used agonist of designer receptors exclusively activated by designer drugs (DREADDs), the compound responsible for visualizing or activating DREADDs in nuclear medicine imaging and at pharmacological doses in murine models remains unclear. In this study, we performed positron emission tomography (PET) imaging and ex vivo autoradiography with 11C-CNO and 11C-clozapine (11C-CLZ) to detect human M4 muscarinic acetylcholine receptor DREADD (hM4D) expression in both a viral vector-injected intracranial mouse model and an original transgenic (Tg) mouse line. PET and autoradiographic images confirmed that both 11C-CNO and 11C-CLZ enabled visualization of hM4D expression in the brain. However, metabolite analysis revealed that the brain concentration of 11C-CLZ was approximately 40 times higher than that of 11C-CNO, while its plasma concentration was only 40% of that of 11C-CNO at 60 min post-injection. In both Tg and non-Tg mice intraperitoneally administered with a pharmacological dose of CNO (1 mg/kg), the ratios of non-radiolabeled CLZ to CNO ranged from 25 to 263 in the brain, whereas the ratios ranged from 0.04 to 0.11 at 30 min and 60 min post-injection in the plasma. Notably, the intraperitoneal administration of a low CLZ dose (0.1 mg/kg) induced a robust neuronal silencing effect exclusively in hM4D Tg mice. These findings clearly demonstrate that CLZ, not CNO, is the primary contributor to in vivo imaging signals and pharmacological effects in murine DREADD models. Additionally, our study confirms that the original hM4D Tg mouse line is a suitable model with stable DREADD expression for developing novel DREADD agonists.